LncRNA OIP5-AS1-directed miR-7 degradation promotes MYMX production during human myogenesis. Issue 12 (23rd June 2022) - Yang, Jen-Hao; Chang, Ming-Wen; Tsitsipatis, Dimitrios; Yang, Xiaoling; Martindale, Jennifer L; Munk, Rachel; Cheng, Aiwu; Izydore, Elizabeth; Pandey, Poonam R; Piao, Yulan; Mazan-Mamczarz, Krystyna; De, Supriyo; et al.
Abstract: Long noncoding RNAs (lncRNAs) and microRNAs (miRNAs) modulate gene expression programs in physiology and disease. Here, we report a noncoding RNA regulatory network that modulates myoblast fusion into multinucleated myotubes, a process that occurs during muscle development and muscle regeneration after injury. In early stages of human myogenesis, the levels of lncRNA OIP5-AS1 increased, while the levels of miR-7 decreased. Moreover, OIP5-AS1 bound and induced miR-7 decay via target RNA-directed miRNA decay; accordingly, loss of OIP5-AS1 attenuated, while antagonizing miR-7 accelerated, myotube formation. We found that the OIP5-AS1 -mediated miR-7 degradation promoted myoblast fusion, as it derepressed the miR-7 target MYMX mRNA, which encodes the fusogenic protein myomixer (MYMX). Remarkably, an oligonucleotide site blocker interfered with the OIP5-AS1 -directed miR-7 degradation, allowing miR-7 to accumulate, lowering MYMX production and suppressing myotube formation. These results highlight a mechanism whereby lncRNA OIP5-AS1 -mediated miR-7 decay promotes myotube formation by stimulating a myogenic fusion program.